Ocena i porównanie wybranych parametrów stabilności postawy u pacjentów z zaburzeniami równowagi i osób zdrowych w badaniach stabilometrycznych = Assessment and comparison of selected parameters of posture stability in patients with balance disorders and healthy people by stabilometric analysis - Jerzy Pyskir; Dorota Ratuszek-Sadowska; Małgorzata Pyskir; Katarzyna Pawlak-Osińska; Iwona Szymkuć-Bukowska; Wojciech Hagner (Kazimierz Wielki University, 2016)
Pyskir Jerzy, Ratuszek-Sadowska Dorota, Pyskir Małgorzata, Pawlak-Osińska Katarzyna, Szymkuć-Bukowska Iwona, Hagner Wojciech. Ocena i porównanie wybranych parametrów stabilności postawy u pacjentów z zaburzeniami równowagi i osób zdrowych w badaniach stabilometrycznych = Assessment and comparison of selected parameters of posture stability in patients with balance disorders and healthy people by stabilometric analysis. Journal of Education, Health and Sport. 2016;6(12):230-242. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.198170 http://ojs.ukw.edu.pl/index.php/johs/article/view/4048         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 22.11.2016. Revised 28.11.2016. Accepted: 09.12.2016.     Ocena i porównanie wybranych parametrów stabilności postawy u pacjentów z zaburzeniami równowagi i osób zdrowych w badaniach stabilometrycznych   Assessment and comparison of selected parameters of posture stability in patients with balance disorders and healthy people by stabilometric analysis   Jerzy Pyskir1,Dorota Ratuszek-Sadowska2, Małgorzata Pyskir2, Katarzyna Pawlak‑Osińska3, Iwona Szymkuć-Bukowska2, Wojciech Hagner2   • Katedra i Zakład Biofizyki, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu • Katedra i Klinika Rehabilitacji, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu • Katedra Otolaryngologii i Onkologii Laryngologicznej, Zakład Patofizjologii Narządu Słuchu i Układu Równowagi, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu       Streszczenie   Wstęp Pionowa stabilna pozycja ciała człowieka jest możliwa dzięki pracy skomplikowanego systemu kontroli postawy, którego praca wymaga prawidłowego działania i współpracy kilku zmysłów. Praca tego układu jest utrudniona w podeszłym wieku, ale także może być zaburzona w wyniku przebytych chorób czy urazów. Istnieje wiele sposobów oceny stabilności posturalnej, ale wypracowanie ogólnych norm różnicujących prawidłową od wadliwej pracy systemu kontroli postawy okazuje się być nadal dużym wyzwaniem. Cel Próba znalezienia takich wartości kilku mierzonych, podczas prostego, krótkiego badania, parametrów, których przekroczenie wskaże na ryzyko wystąpienia zaburzeń pracy systemu kontroli postawy. Materiał i metody W badaniach wzięło udział 50 pacjentów hospitalizowanych w Szpitalu Uniwersyteckim im. dr A. Jurasza oraz 50 zdrowych ochotników. Do badania wykorzystano posturograf firmy PROMED J. Otton. Rejestrowano błądzenie centrum nacisku (COP) na podłoże w czasie swobodnego stania przez 32 sekundy. Badanie obejmowało trzy próby - przy oczach otwartych, zamkniętych oraz samokontrolę. Wyniki Analizowano wartości pola powierzchni i długości statokinezjogramów w trzech sytuacjach pomiarowych oraz współczynniki Romberga i współczynnik koordynacji w badaniu samokontroli. Wszystkie analizowane parametry w grupie pacjentów znacznie różniły się od wyników uzyskanych przez osoby zdrowe. Uwagę zwraca szczególnie powierzchnia SKG przy oczach zamkniętych, współczynnik Romberga i współczynnik koordynacji. Wnioski Wartości pola statokinezjogramu przy oczach zamkniętych przekraczające 400mm2 w czasie 30 sekund badania, jak również wartości współczynnik Romberga powyżej dwóch przy koordynacji wzrokowo - ruchowej na poziomie poniżej 70% powinny skłaniać do podjęcia bardziej szczegółowej diagnostyki systemu kontroli postawy.   Słowa kluczowe: stabilność postawy, system kontroli postawy, posturografia, badanie stabilometryczne, zaburzenia równowagi     Abstract   Introduction Stable vertical position of the human body is possible thanks to the work complicated Postural Control System (PCS), whose operation requires proper cooperation of several senses. Operation of this system deteriorates in the elderly, it also can be impaired as a result of illnesses or injuries. There are a lot of ways of postural stability assessment, but to develop magnitudes of measuring quantities that differentiate normal from malfunctioning PCS appears to be still a large challenge. Aim The aim of this research was trying to find such the values of some measured parameters which indicate the risk of a failure operation of the postural control system. Materials and methods The study involved 50 patients hospitalized in the Dr Antoni Jurasz University Hospital No.1 in Bydgoszcz and 50 healthy volunteers. The PROMED J. Olton company stabilometric platform was used. It was recorded movement center of pressure (COP) on the ground while the free stand for 32 seconds. Each examination included three trials - with eyes open, eyes closed and feedback. Results The values of the area and length of the COP path measured in three trials, Romberg coefficient and the feedback coefficient were compared in both groups. All analyzed parameters in patients group differ significantly from the results obtained by healthy individuals. Special attention should be paid to the COP area with closed eyes, Romberg coefficient and the feedback coefficient. Conclusions The area of sways with eyes closed exceeding 400mm2 in 30 seconds tests, as well as the Romberg coefficient bigger than 2 and the feedback coordination coefficient less than 70% should encourage to take a more detailed diagnosis of postural control system.   Key words: posture stability, Postural Control System (PCS), posturography, stabilometric analysis, balance disorders